Feasibility of Augmented Reality-Based Cognitive Training for Older Adults: The MarketMind AR Approach - Konstantinos Kakoutopoulos; Emmanouil Drakakis; Anastasia Papadopoulou; Christos Goumopoulos (Sensors)
The aging population increases the need for accessible interventions for cognitive training of the elderly to preserve cognitive health. Serious games have been widely used for this purpose, with many existing applications leveraging virtual reality (VR) technology. In contrast, this study explores the potential of augmented reality (AR) for cognitive training. The literature review shows that cognitive training interventions typically employ supermarket-themed serious games that are used extensively in such interventions. MarketMind AR is a supermarket-themed serious game that was created to train memory, attention, and executive function using mobile phone sensors such as cameras, accelerometers, and gyroscopes to interact and recognize the environment. Fifteen older adults participated in a three-attempt trial and completed the System Usability Scale (SUS), the in-game Game Experience Questionnaire (iGEQ), and an adapted version of the Unified Theory of Acceptance and Use of Technology (UTAUT) questionnaires. Qualitative interviews and in-game data (e.g., completion times, PIN recall) were also examined. The results indicated that participants had a positive experience, confirming ease of use, immersive appeal, and perceived cognitive benefits, despite some difficulties with environment scanning and object detection. The results provide evidence that an AR supermarket game leveraging mobile sensors has the potential to be an effective cognitive training tool for older adults.